GNS3 environment in the aspect of testing software for management and monitoring of computer networks - Sierszeń, Artur; Sturgulewski, Łukasz; Janicka, Joanna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The GNS3 environment is a Graphical Network Simulator designed for emulating complex highquality networks that consist of Cisco networking equipment. Devices emulated in GNS3 employ real Cisco Internetwork Operating System (abbreviated as IOS). It allows to examine properties of the Cisco IOS and to verify configurations that need to be implemented later on the Cisco devices. The emulation process takes places in a virtual environment on a personal computer without the need of an actual physical Cisco hardware. The GNS3 is mainly used to visualize the design process of complex network topologies. Therefore, it uses the Scalable Vector Graphics to provide high-quality symbols of Cisco networking equipment. There is a great amount of software for monitoring and managing networks. This kind of applications should be tested before they are purchased. It is usually impossible in a typical network environment; it poses too many risks to the security and functionality ofa network. The Graphical Network Simulator 3 environment is a good solution for testing software and learning how software should be used.
Keywords: management of computer networks; monitoring of computer networks; GNS3 environment; FCAPS reference model; graphical network simulator; network management architecture; graficzny symulator sieci; zarządzanie sieciami komputerowymi; monitorowanie sieci komputerowych; architektura zarządzania siecią